Infrasellar Endoscopic Endonasal Approach for a Pituitary Adenoma Extending into the Third Ventricle, with Anterior Displacement of the Pituitary Gland - Zenonos, Georgios A.; Wang, Eric W.; Fernandez-Miranda, Juan Carlos (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives The current video presents the nuances of the infrasellar endoscopic endonasal approach for a pituitary adenoma extending into the third ventricle, with anterior displacement of the pituitary gland.Design The video analyzes the presentation, preoperative workup and imaging, surgical steps and technical nuances of the surgery, the clinical outcome, and follow-up imaging.Setting The patient was treated by a skull base team consisting of a neurosurgeon and an ENT surgeon at a teaching academic institution.Participants The case refers to 73-year-old female patient who was found to have a sellar mass after failure of vision to improve with cataract surgery. She also reported a several-month history of progressive loss of vision along with daily retro-orbital headaches. The adenoma extended into the clivus as well as in the retrosellar and suprasellar regions, eroding into the floor of the third ventricle. The normal gland was displaced anteriorly.Main Outcome Measures The main outcome measures consisted of reversal of patient symptoms (headaches and visual disturbance), recurrence-free survival based on imaging, as well as absence of any complications.Results The patient's headaches and visual fields improved. There was no evidence of recurrence.Conclusion The infrasellar endoscopic endonasal approach is safe and effective for pituitary adenomas extending into the third ventricle, with anterior displacement of the pituitary gland.The link to the video can be found at: https://youtu.be/zp_06mEyRvY.
Keywords: infrasellar; endoscopic endonasal approach; third ventricular involvement; suprasellar; approach